PIT WATER CHEMICAL COMPOSITION VS TIME FACTOR IN THE CHERVONOHRAD MINING REGION - Voitovych, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the paper is to identify patterns of changes in pit water chemical composition in Chervonohrad mining region conditioned by time, to trace time variations, and determine the factors. The research involved a method of analytical and statistical processing of the pit water geochemical data in Chervonohrad mining region based on Statistica-built diagrams. The analysis of the pit water chemical composition in Chervonohrad mining region concludes the presence of seasonal changes in the pit water chemical composition, and states natural conditions to be essential in forming its chemical composition. There have been studied spatial-temporal changes in the saline composition of the pit water in Chervonohrad mining region, factors that precondition pit water chemical composition, correlation between natural and artificial conditions, and their effects on pit water chemical composition. A practical value of the study is that the data obtained can be used to forecast threats to the environment caused by pit water, to propose ways of water treating, and to predict adverse environmental effects in the areas of similar geological features.